Implementasi Sensor Detak Jantung MAX30100 dan Sensor Konduktansi Kulit GSR menggunakan Mikrokontroller Arduino Pada Alat Pendeteksi Tingkat Stress - Ridtya Anferditya Pratama; Insani Abdi Bangsa; Reni Rahmadewi (Jurnal Ilmiah Wahana Pendidikan, 2021)
In a job in a steel smelting production company, there is a division which must prepare the mental and health of the workers who work in the company. Where the company needs a tool in the form of a foreign health check tool for each worker who mainly works in the production section of the steel smelting section. In that division the workers must be calm and healthy. To make it easier to check the health and raw body of workers, a tool is made in the form of detecting the level of human body tension or the stress level of workers. The whole tool is divided into several parts, namely the android mobile phone, the Arduino Uno R3 microcontroller, the MPX5700AP Pressure Sensor, and the DS18B20 Temperature Sensor. As those who use the tool, it has been made easier, namely that the system is in the form of the Internet of Things (IoT) and can be applied to workers' androids. This tool has been tested and can be used as Stredec Android via a WiFi connection or internet network without having to manually check